2016
DOI: 10.1155/2016/8468594
|View full text |Cite
|
Sign up to set email alerts
|

Fortified Iodine Milk Improves Iodine Status and Cognitive Abilities in Schoolchildren Aged 7–9 Years Living in a Rural Mountainous Area of Morocco

Abstract: Iodine is required for the production of the thyroid hormones essential for the growth and development of the brain. All forms of iodine deficiency (ID) affect the mental development of the child. Our study aims to assess the impact of ID on the intellectual development of Moroccan schoolchildren and to evaluate the effect of consumption of fortified milk on reducing ID. In a double-blind controlled trial conducted on schoolchildren, children were divided into two groups to receive fortified milk (30% of cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The children also cooperated and benefited from the exercise of salt testing and its relevance in a consumer's life. It is scientifically proven that iodine-sufficient children have fine motor skills, information processing, and visual problem solving,[ 12 13 ] and similar results are seen in our study wherein the adequate iodine content in salt was protective for normal and above psychological scores as seen in Table 3 . The results are not significant as the sample size is not representative; however, the inferences can be used as a strong proxy educative message to insist on iodized salt use among the mothers of the school children.…”
Section: Discussionsupporting
confidence: 88%
“…The children also cooperated and benefited from the exercise of salt testing and its relevance in a consumer's life. It is scientifically proven that iodine-sufficient children have fine motor skills, information processing, and visual problem solving,[ 12 13 ] and similar results are seen in our study wherein the adequate iodine content in salt was protective for normal and above psychological scores as seen in Table 3 . The results are not significant as the sample size is not representative; however, the inferences can be used as a strong proxy educative message to insist on iodized salt use among the mothers of the school children.…”
Section: Discussionsupporting
confidence: 88%
“…It is widely accepted that dairy products are a good source of iodine. In a recent study, we have found that non-fortified milk contains large amount of iodine and consumption of this milk during nine months increases considerably the iodine status in school-aged children (Zahrou et al, 2016). In Italy, Watutantrige et al highlighted the benefit effect of milk consumption on iodine status and showed that an adequate iodine status was achieved only when iodized salt was combined with daily milk intake (Watutantrige et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Abdollahpour [41] also revealed that using cognitive strategies were positively correlated particularly with math achievement among male high school freshmen. Similarly, Zahrou [42] found that the consumption of fortified milk has a favorable effect on cognitive ability. Our data suggest that use of cognitive strategies may mediate the association between nutrient status and academic performance.…”
Section: Discussionmentioning
confidence: 99%